2014
DOI: 10.3109/15376516.2014.956910
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of anti-tuberculosis therapy induced hepatotoxicity bySpirulina fusiformis, a candidate food supplement

Abstract: Therapy using Isoniazid (INH) and Rifampicin (RIF) leads to induction of hepatotoxicity in some individuals undergoing anti-tuberculosis treatment. In this study, we assessed the effect of Spirulina fusiformis on INH and RIF induced hepatotoxicity in rats compared with hepatoprotective drug Silymarin. Induction of hepatotoxicity was measured by changes in the liver marker enzymes (aspartate transaminase, alanine transaminase, and alkaline phosphatase). The antioxidant status was also analyzed in liver tissue h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In addition, people with hepatitis C virus (HCV) infection have an increased risk [15, 16]. Some compounds in fruits and food supplements can reduce the risk of AT-DILI due to their abilities to inhibit CYP2E1 activity [17] or to increase anti-oxidative activities [1820]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, people with hepatitis C virus (HCV) infection have an increased risk [15, 16]. Some compounds in fruits and food supplements can reduce the risk of AT-DILI due to their abilities to inhibit CYP2E1 activity [17] or to increase anti-oxidative activities [1820]. …”
Section: Introductionmentioning
confidence: 99%
“…Many factors contribute to the variability of ATLI, including genetic (genetic variations), physiological (age,6 sex7 and race), pathological factors (liver diseases such as HBV/HCV infection8,9) and living habits (dietary compounds,10 smoking11 and alcohol intake12). With the advance of pharmacogenomics (PGx), more attention has been focused on using genomic variants in patient screening and therapy in cancer and other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Although few reports have established a direct link between ATLI risk and UGT2B4 polymorphism, anti‐TB drugs are known to show strong binding and interactions with the transcription factors FXR and can induce cholestatic liver damage by inhibiting its activation . 10,18 Ding Yan et al19 found that reducing the expression of FXR might decrease the expression of UGT2B4 , increase the synthesis of BA, weaken the detoxicating and transporting functions and therefore, mediate the development of cholestatic hepatitis. UGT2B4 was also found to be a novel target gene of the nuclear receptor peroxisome proliferator‐activated receptor alpha ( PPARα ), which might decrease bacterial load and reduce inflammatory responses during mycobacterial infection and along with FXR, induce BA glucuronidation 20,21.…”
Section: Introductionmentioning
confidence: 99%
“…Though there is no suitable drug to weaken the hepatotoxicity effect of TB drugs presently [8], herbs are believed to possess potential hepatoprotective agents [9]. Some plant extracts have been shown to contain constituents that improved antioxidant status which is usually depleted during treatment with TB drugs [10,11]. Many synthetic antioxidants have been shown to produce toxic or mutagenic effects [12], therefore antioxidants from natural sources will be more appropriate for the prevention of TB drugs toxicity [13].…”
Section: Introductionmentioning
confidence: 99%